Metales y aleaciones en odontología - Giraldo-R., Olga Lucía (Revista Facultad de Odontología Universidad de Antioquia, 2009)
Knowledge of the various dental materials used in Prosthodontics is a paramount necessity for professionals in dentistry. Several metals are routinely used in dentistry for a variety of applications, including the fabrication of dentures, temporary and permanent crowns, orthodontic brackets, and direct tooth restorations. The metals most commonly used are gold, nickel, cobalt, chromium, tin, aluminum, titanium, iron, palladium, platinum, cooper, silver, vanadium, and mercury. The different alloys used for prosthetic restoration have notably increased for the past 25 years, thus the choice of a particular alloy for a given clinical situation has become a difficult decision to make. A number of properties, including resistance, hardness, elastic module, micro structural phases, grain size, corrosiveness, thermal expansion coefficient, oxidation and color, are relevant to the appropriate choice of a given alloy, being the patient’s bio-safety the most important one. The decision on the selection of one particular alloy has profound health, financial, legal and technical implications, as well as the practitioner’s satisfaction and the health of the patient.